PENGARUH LIKUIDITAS, SOLVABILITAS, PROFITABILITAS, NILAI PASAR, DAN PEMANFAATAN ASET TERHADAP FINANCIAL STATEMENT FRAUD - Bustanul Arifin; Nana Nofianti; Han Fajri Kautsar (FEB Universitas Sultan Ageng Tirtayasa, 2016)
The purpose of this study is to examine the effect of liquidity, solvency, profitability, market value, and assets utilization of fraudulent financial statements. Accounting data were obtained from the reported financial statement of 44 sampled public companies of five (5) years (2010-2014). The statistic instrument employed was pooled data binary logistic regression. Data collected were run with SPSS 23. The finding revealed that solvency, profitability, market value, and assets utilization were significanty related to the financial statement fraud. It was recommended that accounting ratio should be critically by investor and creditor Keyword : Liquidity, Solvability, Profitability, Market Value, Assets Utilization, frauds, Accounting Ratio